Effect of sulphur levels on growth, yield and quality of Indian mustard (Brassica juncea) genotypes - Pachauri, Raman Kumar; Trivedi1, S.K. (Annals of Agricultural Research, 2014)
A field experiment was conducted during winter season of 2008-09 and 2009-10 on sandy loam soil Bichpuri, Agra to find out the effect of sulphur levels on growth, yield and quality of Indian mustard [Brassica juncea (L.), Czernj and Cosson] genotypes. The treatments consisted of four genotypes (Pusa Bold, ’Rohini’, ’Varuna’ and ’Kranti’) of mustard and four levels of sulphur (0, 30, 60 and 90 kg/ha) applied through elemental sulphur in factorial randomized block design replicated thrice. Pusa Bold genotype recorded the highest seed yield of 2.05 and 2.09 t/ha followed by ’Varuna’, ’Rohini’ and ’Kranti’ respectively. Significant response was observed up to 90 kg S/ha in seed and stover yield. Oil content and nutrient uptake were also highest under this treatment. ’Pusa Bold’ gave highest net return of Rs. 39575 followed by ’Varuna’, ’Rohini’ and ’Kranti’, respectively. Highest net returns of Rs. 42,018 was recorded with the application of 90 kg S ha. However, net return/Rs. invested (3.35) was higher at 60 Kg S/ha.